Cyberchondria during the COVID-19 pandemic: Its relationship with health anxiety, state anxiety and trait anxiety - Ortega Germosén, Gianluis; Bello-Castillo, Iris; Sánchez-Vincitore, Laura (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Introduction: Cyberchondria is a compulsive cycle of seeking medical information that, instead of satisfying the need for information, increases anxiety. Objective: This cross-sectional study explored how health anxiety, trait anxiety, and state anxiety impact the levels of cyberchondria in young Dominicans during the COVID-19 pandemic. We investigated the differences between people who are considered to be at risk for complications from COVID-19 and those who are not in these variables. Method: 87 participants answered an online booklet: A sociodemographic section; State-trait anxiety questionnaire (STAI); Brief Health Anxiety Inventory (SHAI); Short version of the Cyberchondria severity scale (CSS-12). Results: A multiple regression analysis with forward selection found that the best fit model of cyberchondria selected two predictors: health anxiety (β = .38, p < .001) and trait anxiety (β = .28, p = .004), explaining 25% of the variance (p < .001). People who believe are at risk of complications from COVID-19 are 4.77 times more likely to meet diagnostic criteria for hypochondriasis than those who do not think that are at risk. Discussion and conclusion: High levels of health anxiety and trait anxiety is associated with cyberchondria and hypochondriasis, specifically in people at risk of complications from COVID-19, representing a threat to public health that must be intervened to moderate its social and economic impact.